Law Enforcement Against Environmental Damage and Pollution by Mining Companies - Berlianty, Teng; Holle, Erick Stenly; Ternate, Fandi Ahmad (Fakultas Hukum Universitas Pattimura, 2026)
Introduction: The environment inhabited by humans must be a good and healthy environment, far from pollution and damage, so that humans can continue their lives in this world.Purposes of the Research: The objectives of this study are: To study and analyze the responsibility of companies that pollute the environment in Central Halmahera, North Maluku Province.Methods of the Research: The type of research conducted in this paper is normative juridical law research that is descriptive and analytical. Normative legal research is a form of legal writing that is based on the characteristics of normative law. The approach used is a statutory approach or a juridical approach, namely research on legal products, and a conceptual approach. This approach is carried out because there is no legal regulation for the problems discussed. This conceptual approach starts from the views and doctrines that have developed in legal science, resulting in an understanding of the law and legal principles that are relevant to the problems discussed.Results of the Research: The results of this study show that the responsibility of the nickel mining company PT Indonesia Weda Bay Industrial Park (IWIP) which is suspected of environmental pollution that occurs includes preventive measures, waste management and recovery if environmental damage occurs, then business actors are absolutely responsible. Civil Liability of the nickel mining company PT Indonesia Weda Bay Industrial Park (IWIP) includes installing a waste management unit so that the waste is in accordance with the specified environmental quality standards, restoring environmental functions, increasing supervision and evaluation to anticipate the recurrence of negligence and carrying out moral responsibility to the environment by accelerating the process of restoring polluted river stream environments by carrying out Routine cleaning of river flows so that the remains of waste that comes out into the river can be quickly decomposed.